Aquinas on friendship - Schwartz, Daniel, 1972- (Oxford : Clarendon, 2007)
Daniel Schwartz presents and examines the thoughts of the great medieval philosopher Thomas Aquinas on the subject of friendship - the ideal type of relationship that rational beings should cultivate.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Friendship -- Philosophy